The interrelation of the level of somatic cells in milk at the end of lactation with fertility and milk yield of Ayrshire cows in the conditions of the European North of Russia - Komlyk Irina; Grishina Natalia (BIO Web of Conferences)
The work studies the influence of the somatic cell level in milk in the last months of lactation on the indices of reproduction and productivity of cows in the subsequent lactation. To study this problem, we used a database of a herd of highly productive purebred Ayrshire cattle of a large farm in the North of Russia. The average milk yield was 8000 kg of milk. The indices of reproductive capacity of cows (indifference period, insemination period, service period, conception index, conception rate after the first insemination, early embryonic mortality) were analyzed. The change in the number of somatic cells in dynamics during the whole lactation in cows of different ages was studied. It has been established that the number of somatic cells in milk can serve as an indirect assessment of the udder condition. Our study revealed a complex, ambiguous relationship between the level of somatic cells and reproductive qualities. Inflammation of the udder in the last months of lactation before the dry period can increase the risk of decline of reproductive indicators in the postpartum period, increasing the degree of embryonic mortality. It has been determined that first-calf heifers are less likely to suffer from udder diseases. However, the negative impact of mastitis on subsequent fertility in young animals is higher than in mature cows.